2021
DOI: 10.3390/microorganisms9102093
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation Effects of Bifidobacterium animalis subsp. lactis XLTG11 on Dextran Sulfate Sodium-Induced Colitis in Mice

Abstract: Inflammatory bowel disease (IBD) is a chronic immune-related disease, which can occur through the dysfunction of the immune system caused by the imbalance of gut microbiota. Previous studies have reported the beneficial effects of Bifidobacterium on colitis, while the related mechanisms behind these effects have not been fully elucidated. The aim of our study is to investigate the alleviation effect of Bifidobacterium animalis subsp. lactis XLTG11 (B. lactis) on dextran sulfate sodium (DSS)-induced colitis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
6
17
0
Order By: Relevance
“…We further observed a positive modulatory effect of B. lactis BLa80 on the gut microbiota in mice with UC. Our results are consistent with recent findings showing that B. lactis XLTG11 can attenuate DSS-induced UC in a process associated with inhibition of signalling through the TLR4/MYD88/NF-κB pathway, modulation concentrations of inflammatory cytokines, and remodelling of the gut microbiota (Wang et al 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…We further observed a positive modulatory effect of B. lactis BLa80 on the gut microbiota in mice with UC. Our results are consistent with recent findings showing that B. lactis XLTG11 can attenuate DSS-induced UC in a process associated with inhibition of signalling through the TLR4/MYD88/NF-κB pathway, modulation concentrations of inflammatory cytokines, and remodelling of the gut microbiota (Wang et al 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, we observed that the probiotic consortia ameliorated the symptoms of mice with DSS-induced colitis, as evidenced by a reduction in shortened colon length, weight loss, DAI score, mucosal loss, and inflammatory cell infiltration, which are in accordance with previous studies ( 37 , 49 51 ). Additionally, IHC revealed a reduction in F4/80 + macrophages in the probiotic consortia group.…”
Section: Discussionsupporting
confidence: 92%
“…lactis XLTG11 could adjust the composition of the intestinal flora and significantly alleviate gastrointestinal related diseases. 16…”
Section: Introductionmentioning
confidence: 99%
“…lactis XLTG11 could adjust the composition of the intestinal flora and significantly alleviate gastrointestinal related diseases. 16 Ampicillin is a widely used kind of sesgalactosamine. It has an inhibitory effect on a variety of Gram-positive and Gramnegative bacteria, and has broad-spectrum activity against various bacterial groups.…”
Section: Introductionmentioning
confidence: 99%